Pengelolaan Lembaga Pendidikan Unggul: Analisis Manajemen Strategis Fred R. David di SD Muhammadiyah 1 Bandar Lampung - Junaidah; Yola Arjunita Putri; Mayang Sari (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
To remain competitive, educational institutions must develop and sustain a competitive advantage. This study examines strategic management as a driver of competitive advantage, with a specific focus on strategic formulation, implementation, and evaluation based on Fred R. David’s framework. The research employs a qualitative, descriptive approach, utilizing observation, interviews, and documentation at Muhammadiyah 1 Elementary School in Bandar Lampung to analyze how the institution is managed to achieve competitive advantage. The findings reveal that strategic formulation at the school is conducted systematically through a participatory process that engages all stakeholders, aligning with strategic management theory that positions every school component as a critical factor in decision-making. Strategic implementation emphasizes innovative instruction grounded in deep learning principles, dynamic curriculum development, including Indonesia’s Independent Curriculum (Kurikulum Merdeka) and holistic marketing strategies that leverage social media alongside reward systems for teachers and students. Collectively, these initiatives enhance educational quality, strengthen the school’s appeal, and increase student enrollment. Strategic evaluation is carried out comprehensively and continuously, focusing on teacher performance, parent satisfaction, and alignment with the school’s vision and mission. This process supports adaptive decision-making and reinforces the school’s competitive positioning amid shifting educational landscapes. This study offers a novel empirical contribution to Islamic basic education by integrating deep learning pedagogy, community-based marketing, and feedback-driven evaluation within a unified strategic management framework, while also proposing a value-centered integrative model for sustainable quality.